Pengembangan Student’s Metacognitive Awareness Scale (SMAS) pada Siswa Di Indonesia - Mahyiyuddin, Abiyyu Arib (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
This study aims to develop a scale that measures students' metacognitive awareness, called the Student's Metacognitive Awareness Scale (SMAS). Data collection was carried out for 13 days, starting from March 24, 2025 to April 6, 2025, in Senior High Schools (SMA) and Vocational High Schools (SMK). The respondent criteria were high school/vocational high school students aged 15-18 years. A total of 212 students filled out the measuring instrument, with 208 data that could be processed. Of the initial 52 items, 24 items survived until the end. Content validation using the Aiken's V formula obtained a value of 0.92 - 1. The item discrimination power moved from 0.76 - 0.86. The McDonald's Omega reliability coefficient obtained was 0.980. Confirmatory Factor Analysis (CFA) showed that the model was fit, with a loading factor range of 0.89 - 1.14. The results of this study indicate that SMAS is a valid and reliable measuring tool for assessing students' level of metacognitive awareness.